Pengaruh Promosi dan Harga terhadap Keputusan Pembelian pada PT.Sari Burger Indonesia - Vira Soraya; Husni Mubarak (Journal of Trends Economics and Accounting Research, 2022)
The purpose of this study was to determine whether there was an influence of promotion and price on purchasing decisions at PT. Sari Burger Indonesia. The sample of this study was 97 people, taking samples using accidental sampling techniques (accidental sampling), namely sampling techniques where the researcher took samples of anyone who was at the place or accidentally met as a sample that was considered suitable as a data source. Data analysis using Multiple Regression Test, hypothesis testing using the coefficient of determination test (R2), partial test (t test) and simultaneous test (F test), while processing data using SPSS 20. The results of this study indicate that promotion and price can explain the diversity of Purchasing decision variables, besides, partially promotion variables have a positive and significant effect on purchasing decisions while the price variable has no effect and is not significant on purchasing decisions, while simultaneous promotions and prices have a positive and significant effect on purchasing decisions at PT.Sari Burger Indonesia